2022
DOI: 10.1177/15533506211073417
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Fluorescence Image-Guided Surgery in Esophageal and Gastric Cancer Operations

Abstract: Background Near-infrared fluorescence image-guided surgery helps surgeons to see beyond the classical eye vision. Over the last few years, we have witnessed a revolution which has begun in the field of image-guided surgery. Purpose, and Research design Fluorescence technology using indocyanine green (ICG) has shown promising results in many organs, and in this review article, we wanted to discuss the 6 main domains where fluorescence image-guided surgery is currently used for esophageal and gastric cancer surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…In recent years, ICG fluorescence imaging for LNs tracing has attracted surgeons' attention and ICG imagingguided lymphadenectomy has been introduced in GC surgery (9)(10)(11). Until now, several studies have reported that ICG imagingguided lymphadenectomy was applied to GC surgery and showed promising results in increasing the number of retrieved LNs, without increasing operative time and overall complications (12)(13)(14). However, whether ICG imaging-guided lymphadenectomy is indeed beneficial for LNs dissection remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, ICG fluorescence imaging for LNs tracing has attracted surgeons' attention and ICG imagingguided lymphadenectomy has been introduced in GC surgery (9)(10)(11). Until now, several studies have reported that ICG imagingguided lymphadenectomy was applied to GC surgery and showed promising results in increasing the number of retrieved LNs, without increasing operative time and overall complications (12)(13)(14). However, whether ICG imaging-guided lymphadenectomy is indeed beneficial for LNs dissection remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple clinical studies have been conducted on intraoperative uorescence imaging for esophageal cancer. The results have demonstrated the advantages of this technology in the accurate identi cation and dissection of esophageal cancer lymph nodes [31][32][33][34].…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, multispectral visualization of different lymphatic regions of interest using combinations of fluorophores has also been studied 59 . Fluorescent visualization of sentinel nodes has not only been described for breast cancer and melanoma, but also other malignancies, including gynaecological, gastrointestinal, endocrine, head and neck, and urological malignancies 60–65 .…”
Section: Lymph Node Targetingmentioning
confidence: 99%